Behcet's disease associated with myelodysplastic syndrome: a case report. - Oh, E. J. (Korean Academy of Medical Sciences, 1999)
A rare case of Behcet's disease associated with myelodysplastic syndrome (MDS) is described. A 50-year-old Korean female suffering recurrent oral ulcer, genital ulcer, fatigue, arthralgia in both knees and fever was diagnosed as Behcet's disease. The findings of bone marrow aspirates were consistent with refractory anemia, a subtype of myelodysplastic syndrome. Chromosomal analysis of bone marrow cells revealed 46,XX,-8,-20,+der(8)t(8;20)(p23;p10),+der(8) t(8;20)(p23;q10)[30]. The chromosomal changes found in this patient were different from those of previous reports, which mostly revealed trisomy 8. If anemia, low reticulocyte count and dyspoietic cells are sustained in Behcet's disease, physicians should be alert to the possibility of MDS with aberration in chromosome 8 and perform a bone marrow study for the proper diagnosis and treatment of the disease. We presented a case of Behcet's disease associated with MDS, which is the first Korean case.